Functions of plants for ibuprofen removal in constructed wetland - Suriani Kamsan (2014)
Pharmaceutical compound have been detected in water bodies and the significance in the environment poses potential threats to public and environmental health. The traces of compound in water bodies were introduce through various sources such as municipal wastewater and improper disposal of medication in sewage system. This study will focus on the removal mechanism and efficiencies of Ibuprofen (IBU), a common anti-inflammatory drug, in constructed wetland (CW).